2016
DOI: 10.1590/1414-431x20154616
|View full text |Cite
|
Sign up to set email alerts
|

Negative emotions affect postoperative scores for evaluating functional knee recovery and quality of life after total knee replacement

Abstract: This study aimed to determine whether psychological factors affect health-related quality of life (HRQL) and recovery of knee function in total knee replacement (TKR) patients. A total of 119 TKR patients (male: 38; female: 81) completed the Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), State Trait Anxiety Inventory (STAI), Eysenck Personality Questionnaire-revised (EPQR-S), Knee Society Score (KSS), and HRQL (SF-36). At 1 and 6 months after surgery, anxiety, depression, and KSS scores in TKR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 34 publications
0
22
0
1
Order By: Relevance
“…The evidence presented with a number of strengths (Supplementary Table 2); for example, each included study had a focused objective. Three papers [ 4 , 20 , 23 ] failed to identify a gap in the existing literature. All outcome measures were validated.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The evidence presented with a number of strengths (Supplementary Table 2); for example, each included study had a focused objective. Three papers [ 4 , 20 , 23 ] failed to identify a gap in the existing literature. All outcome measures were validated.…”
Section: Resultsmentioning
confidence: 99%
“…Hirschmann et al [ 10 ] found that higher levels of pre-operative trait anxiety predicted greater pain (Spearman’s rho = 0.25; p < 0.05) and stiffness (Spearman’s rho = 0.26; p < 0.05). Qi et al [ 23 ] demonstrated that pre-operative anxiety as measured by the Trait Anxiety Inventory (TAI) predicted poorer knee function at 6 months.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both THA and TKA are often reported to improve physical functioning and HRQoL (Czyzewska, Glinkowski, & Walesiak, 2014;Elmallah et al, 2016;Rat et al, 2010). At the same time, anxiety preceding TJA affects the postoperative functional status, satisfaction with joint replacement, general quality of health index, and increases the risk of complications, and pain, along with the experience of pain up to two years after surgery (Khatib, Jenkin, Naylor, & Harris, 2016;Khatib, Madan, Naylor, & Harris, 2015;Gill & Mc-Burney, 2013;Qi et al, 2016;Rasouli, Menendez, Sayadipour, Purtill, & Parvizi, 2016;Singh & Lewallen, 2013;Vissers et al, 2012). Ayers with coworkers (2004) observed that the preoperative mental component of the HRQoL measurement predicted the score of the physical component of the same tool six months after surgery, indicating the need for longterm emotional support to enhance patient recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Its prevalence associates with aging and gender. According to the World Health Organization, OA is commonly regarded as the most important cause of function disability (1)(2)(3)(4). Current treatment of OA aims to improve pain and function and enhance quality of life (5).…”
Section: Introductionmentioning
confidence: 99%